Pós-venda em concessionárias líderes de vendas de veículos 0Km: uma análise das melhores práticas - Souza, Marcelo Alves de (Universidade do Vale do Rio dos Sinos, 2017)
This research approaches the issue of obtaining results in car dealerships which are leaders in selling 0 km vehicles that practice and obtain after-sales results. The objective of this study is to analyze and compare the practices the car dealerships which are leaders in selling 0 km vehicles based in Rio Grande do Sul, permeating the conceptual after-sales model: product support, customer relationship and management and resources. In order to fulfill this proposal, a bibliographic research was carried out to provide a theoretical basis for the study and it was used a case study as the research method. The data collection was done through semi-structured interviews with executives from 10 car dealerships of different brands. The indicators of these companies were also collected for entry vehicles. The management contribution enabled the elaboration of a theoretical model and the discussion of the after-sale application. The management contribution focuses on the identification of the best after-sales practices verified in the best performing dealerships in terms of quality and profitability.
Keywords: Pós-venda; Indicadores concessionário automotivo; Práticas concessionário automotivo; After-sales; Car dealership; Indicators of car dealership; Practices of car dealership; ACCNPQ::Engenharias::Engenharia de Produção